How and Why a Bit-Wise Neutrality with and without Locality Affects Evolutionary Search - GALVAN-LOPEZ, EDGAR (ACM Press, 2007)
Despite the vast work on neutrality, there are not general conclusions on its effects. In this paper we make an effort to understand how neutrality in uences evolution. For this purpose we will use a type of neutrality that allows locality (which is believed to be a desirable feature of neutrality).
PUBLISHED
Keywords: Applied mathematics; neutrality